Uremic solutes of indoxyl sulfate and p-cresol enhance protease-activated receptor-2 expression in vitro and in vivo in keratinocytes. (January 2021) - Kim, SJ; Zhang, X; Cho, SB; Kim, CH; Park, HC; Moon, SJ
Objectives: Uremic pruritus is common in patients with chronic kidney disease (CKD). The retention of uremic solutes is thought to be associated with uremic pruritus. Meanwhile, activation of protease-activated receptor-2 (PAR-2) has been suggested to play an important role in pruritus. The present study was performed to investigate the effects of uremic solutes on the expression of PAR-2 in the skin. Methods: Indoxyl sulfate (IS), p -cresol (PC), and uremic sera from CKD patients were used to stimulate PAR-2 expression in normal human epidermal keratinocytes (NHEKs). Also, NHEKs were additionally pretreated with soybean trypsin inhibitor to evaluate its inhibitory effect on PAR-2 expression. Patterns of cutaneous PAR-2 expression were investigated in skin samples from five CKD patients and CKD mice. Results: In NHEKs, IS, PC, and sera from CKD patients significantly induced PAR-2 mRNA and protein expression. Soybean trypsin inhibitor significantly decreased PAR-2 mRNA and protein expression in NHEKs treated with IS, PC, and CKD sera. NHEKs treated with IS and PC exhibited significant increases in protease activity. Skin from both CKD patients and mice exhibited marked upregulation of PAR-2 expression compared to control skin. Conclusions: Results from the present study suggest that uremic solutes either directly or indirectly affect PAR-2 expression in the skin of CKD subjects, potentially playing an important role in the pathogenesis of uremic pruritus.